Workplace Politics and Employee’s Job Performance: Mediating Role of Job Stress, Evidence from Degree Awarding Institutions of Sindh, Pakistan - Soomro, Sajan Khan (International Journal of Psychosocial Rehabilitation, 2020)
Integrated with the P-E Fit theory of stress, this research investigates workplace politics and employees’ job performance relationship through the mediating role of job stress. A proposed mediation model was tested by collecting supervisor rated survey data through a close-ended questionnaire from 195 participants of different DAI’s of Benazirabad, Sindh, Pakistan. Data of this study has been analyzed by using SPSS and Smart-PLS software, with regression and bootstrapping methods to test the proposed hypothesis of this study. Our results suggest that job stress mediates the relationship between workplace politics and employees’ job performance. Moreover, the findings of our study indicate that workplace politics also become the cause of stress at the workplace and it harms the individuals psychologically that decrease the performance of individuals. Theoretical and practical implications are discussed separately especially for the public and private DAI’s.